The Little Green Data Book 2013 - World Bank; World Bank. (Washington, D.C. The World Bank, 2013)
The Little Green Data Book is a pocket-sized ready reference on key environmental data for over 200 countries. Key indicators are organized under the headings of agriculture, forestry, biodiversity, oceans, energy, emission and pollution, and water and sanitation. The 2013 edition of The Little Green Data Book introduces new set of ocean-related indicators, highlighting the role of oceans in economic development.
Electronic reproduction.
Keywords: Economic development -- Statistics; Economic history -- 1990 -- Statistics; Economic indicators; Social indicators; Electronic books